Implementasi Model Pembelajaran IPS Terpadu (Suatu Studi Evaluatif di Smp Kota Surakarta) - Leo Agung S. (Jurnal Pendidikan dan Kebudayaan, 2012)
The objective of this study is: 1) to obtain information in relation to the implementation of instructional model of integrated social science at Junior Secondary School in Surakarta City; 2) to identify the inhibiting factors; and 3) to know some efforts performed by Social Science teachers to enhance their professionalism. This study is an evaluation study using qualitative-descriptive research method. This research tends to use a single case study. The subject of this research is Social Science teachers of SMP/MTs (Junior Secondary School/Islamic Junior Secondary School) in Surakarta City. The data was collected through interviews, observation, and archival records and documents. The findings showed that: 1) there were still many differences in the implementation of Social Science instruction at SMP/MTs. There were teachers who delivered Social Science in integrated way, semi integrated and partially; 2) there were many obstacles faced by the teachers, among others: (a) lack of understanding/mastery of the material outside their competency, (b) lack of knowledge and understanding of instructional models of Integrated Social Science, (c) difficulties to apply the instructional concepts of Integrated Social Science, and (d) a skeptical attitude of Social Science teachers; 3) some efforts performed by Social Science teachers to improve their professionalism, among others: (a) asking other Social Science teachers, (b) reading Social Science-related reference books, (c) attending training, socializaion, seminar, workshop, and (d) sharing experiences. ABSTRAK Penelitian ini bertujuan untuk: 1) mengetahui implementasi model pembelajaran IPS Terpadu di SMP Kota Surakarta; 2) mengidentifikasi faktor-faktor penghambat, dan 3) mengetahui upaya-upaya yang dilakukan oleh guru IPS dalam meningkatkan profesionalisme.Penelitian ini merupakan studi evaluasi dengan menggunakan metode penelitian deskriptif kualitatif. Bentuk penelitian cenderung menggunakan studi kasus tunggal. Subyek penelitian, yaitu guru-guru IPS di SMP/MTs Kota Surakarta.Teknik dan alat pengumpul data yang digunakan, yaitu: wawancara, observasi, dan mencatat arsip serta dokumen. Hasil penelitian menunjukkan bahwa: 1) dalam implementasinya pembelajaran IPS di SMP/MTs masih terdapat banyak perbedaan. Ada yang melaksanakan pembelajaran IPS terpadu secara penuh, setengah terpadu, dan tidak terpadu; 2) hambatan yang dihadapi, antara lain: (a) kurang pemahaman/penguasaan terhadap materi di luar bidangnya; (b) kurangnya pengetahuan dan pemahaman model model pembelajaran IPS Terpadu; (c) kesulitan dalam menerapkan konsep pembelajaran IPS Terpadu;dan (d) sikap skeptis dari guru IPS itu sendiri; 3) upaya yang dilakukan guru IPS dalam meningkatkan kompetensi profesionalnya, antara lain: (a) bertanya kepada guru IPS yang lain; (b) membaca bukubuku referensi tentang IPS; (c) mengikuti pelatihan, sosialisasi, workshop, seminar, semiloka; dan (d) berbagai (sharing) pengalaman.